2022
DOI: 10.7759/cureus.27201
|View full text |Cite
|
Sign up to set email alerts
|

CD 5+ Peripheral B Cell Lymphoma With Transformation to CD 5+ Diffuse Large B Cell Lymphoma in the CNS: A Case Report Treated With Rituximab, High Dose Methotrexate, Cytarabine, and Intrathecal Methotrexate

Abstract: B-cell non-Hodgkin’s lymphoma includes several subtypes, notably Diffuse Large B-Cell Lymphoma (DLBCL), the most common B-cell subtype. Each presentation has its defining characteristic, of which CD5 positivity is notoriously known for being a poor prognostic factor. CD5 positivity has a high female preponderance, more commonly involves the bone marrow, presents with higher LDH levels and B symptoms on presentation, and stage 3-4 on the diagnosis. The exact incidence of CD5+ DLBCL arising from Chronic Lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[23,24] In addition, each presentation has its defining characteristic, of which CD5 positivity is notoriously known for being a poor prognostic factor. [21] Our patient was considered to have a good outcome, being considered disease free after periodic clinical and paraclinical testing, and being referred to the surgery clinic for removal of the iliac anus and restoration of digestive continuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,24] In addition, each presentation has its defining characteristic, of which CD5 positivity is notoriously known for being a poor prognostic factor. [21] Our patient was considered to have a good outcome, being considered disease free after periodic clinical and paraclinical testing, and being referred to the surgery clinic for removal of the iliac anus and restoration of digestive continuity.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jain et al [20] , CD5 positivity is classically associated with a poor prognostic factor, having female preponderance, more bone marrow involvement, higher LDH levels, B symptoms on presentation, and Ann Arbor stage 3 to 4 on diagnosis. [21] In this current case, based on the morphology and immunophenotype, we present a case of a young male patient with a diagnosis of AIDS-related diffuse large B cell lymphoma, CD5-positive, with a high LDH level and stage IV Ann Arbor at presentation. Using the Hans algorithm, we concluded that the cell of origin was a non-GCB.…”
Section: Discussionmentioning
confidence: 99%